METHODS FOR TEACHING YOUNG SWIMMERS SPECIAL WATER EXERCISES - Sulaymonov M. (Proximus Journal Publishing, 2024)
This article provides the necessary information about swimmers lying on the water, transitioning to a vertical position, transitioning from a standing position to a vertical position, transitioning from a standing position to a vertical position, lying on a wheel, lying on a wheel, swinging legs by the pool wall, swinging legs by the pool wall, and sliding with the help of the swimming position.
Keywords: Water; lying; standing; wet